2020
DOI: 10.1021/acs.inorgchem.0c02956
|View full text |Cite
|
Sign up to set email alerts
|

Multireference Ab Initio Investigation on Ground and Low-Lying Excited States: Systematic Evaluation of JJ Mixing in a Eu3+ Luminescent Complex

Abstract: A theoretical protocol combining density functional theory (DFT) and multireference (CAS) calculations is proposed for a Eu3+ complex. In the complex, electronic levels of the central Eu3+ ion are correctly calculated at the CASPT2 level of theory, and the effect of introducing different numbers of states in the configuration interaction matrices is highlighted as well as the shortcomings of DFT methods in the treatment of systems with high spin multiplicity and strong spin–orbit coupling effects. For the 5D0 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 67 publications
1
11
0
Order By: Relevance
“…Examination of methods reported in the literature revealed very few attempts to capture the LMCT character and/or energies of excited states of lanthanoid complexes, in marked contrast to the larger amount of work dedicated to the theoretical treatment of charge transfers in d-block metals complexes. For instance, in a recent ab initio multireference computational study of the 4f–4f excitations responsible for the luminescence of Eu III β-diketonate complexes, it was shown very convincingly that the energies of the emitting 5 D J multiplets in Eu III are much more sensitive than the ground-state 7 F J levels to the effects of spin–orbit coupling, inducing a strong mixing of various multireference Russell–Saunders terms, which necessitates the inclusion of not only septets and quintets in the calculation, but also of relevant triplets and singlets. Remarkably, in the same study, it was also shown that TD-DFT with an asymptotically corrected exchange potential (LB94), despite the complete absence of any spin–orbit coupling description, also appears to provide a reasonable estimate of the 5 D J multiplets excitation energies, in clear contradiction with the basic electronic structure theory at play.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Examination of methods reported in the literature revealed very few attempts to capture the LMCT character and/or energies of excited states of lanthanoid complexes, in marked contrast to the larger amount of work dedicated to the theoretical treatment of charge transfers in d-block metals complexes. For instance, in a recent ab initio multireference computational study of the 4f–4f excitations responsible for the luminescence of Eu III β-diketonate complexes, it was shown very convincingly that the energies of the emitting 5 D J multiplets in Eu III are much more sensitive than the ground-state 7 F J levels to the effects of spin–orbit coupling, inducing a strong mixing of various multireference Russell–Saunders terms, which necessitates the inclusion of not only septets and quintets in the calculation, but also of relevant triplets and singlets. Remarkably, in the same study, it was also shown that TD-DFT with an asymptotically corrected exchange potential (LB94), despite the complete absence of any spin–orbit coupling description, also appears to provide a reasonable estimate of the 5 D J multiplets excitation energies, in clear contradiction with the basic electronic structure theory at play.…”
Section: Resultsmentioning
confidence: 99%
“…Remarkably, in the same study, it was also shown that TD-DFT with an asymptotically corrected exchange potential (LB94), despite the complete absence of any spin–orbit coupling description, also appears to provide a reasonable estimate of the 5 D J multiplets excitation energies, in clear contradiction with the basic electronic structure theory at play. This unprecedented study of the role of spin–orbit coupling in the ab initio description of Eu III excited states exposes the risk with DFT methods of obtaining seemingly good results due to accidental cancellation of errors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ground-state term symbol for the Eu 3+ ion is 7 F, which is split into seven different J states ( 7 F 0‑6 ) by spin–orbit coupling, λ. The 7 F 0 state is the ground state and the first excited state, 7 F 1 , is typically found to lie approximately 350 cm –1 above the 7 F 0 ground state. This 7 F 1 excited state can therefore be thermally populated and can also mix, via out-of-state spin–orbit coupling, with the 7 F 0 ground state. The latter effect leads to TIP. The full spin-Hamiltonian is given by eq .25ex2ex = Zeeman + SO + CF with the 7 F 1 excited state being split in zero applied magnetic field by a low-symmetry crystal field described by the following Hamiltonian , .25ex2ex CF = i = 1 N k = 2 , 4 , 6 q = k k σ i k B k i q θ k k i q …”
Section: Resultsmentioning
confidence: 99%
“…Among processes involving them, triplets are of paramount importance in the so-called antenna effect for the sensitization of lanthanide (Ln) ion emission, as the energy gap between triplet and Ln 3+ emitter levels is one of the key factors ruling the emission properties . For instance, lanthanide luminescence-based thermometric features are tightly bound to the triplet state energy, in particular when the back-energy transfer is considered. Besides its energy, the design of novel luminescent systems with tailored properties requires a detailed knowledge of the triplet spin distribution over the molecular skeleton. Indeed, energy transfer pathways are sometimes directly influenced by the specific spatial distribution of the spin density in the sensitizer ligand and by the triplet energy. Moreover, the delocalization of the triplet state spin density can be related to the phosphorescence quantum yield, whose control is crucial in technological applications such as organic light-emitting diodes …”
Section: Introductionmentioning
confidence: 99%